Strengthening the Role of Community Health Workers and Digital Innovation in Stunting Prevention in Nagari Dusun Baru Tapan, Pesisir Selatan Regency, West Sumatra Province - Masnarivan, Yeffi; Ramadhan, Nugraha; Muchtariza, Suci; Rivan, Yoko Masna; Rasyid, Zul Azizir; Putri, Helga Eka; Gumilang, Yuza Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Stunting is still a public health problem in Indonesia, particularly in one with less of nutrition and health knowledge. It results in long-term impacts on learning, cognitive development, productivity, and risk of noncommunicable diseases. The relationship between home visits by community health workers and the concomitant effect of digital innovations to prevent stunting can be seen in this study, where it was conducted in Nagari Dusun Baru Tapan, Pesisir Selatan, West Sumatra. These community services were incorporated into the 2025 Community Service Program of Andalas University which included promo-gizi, local processed food processing training and monitoring of nutritional status in toddlers using Android-based application GiziAnakKu. The program was centered around 1,000 days of life as a crucial window period for child development through nutrition, including the practice of exclusive breastfeeding and complementary feeding and balanced diet behaviors. Results from surveillance showed that most of the toddlers possessed acceptable nutrition (85.3%), however, 14.7% were stunted and 8.8% had an increased risk of overnutrition indicating double burden of malnutrition. Attendees appreciated the training and reinforced the value of sustainable community-based intervention. Through empowerment of community health workers and use of digital technology, the present study adds to definitions for comprehensive stunting prevention that can become best practice in similar areas.